Cornelia Parker - Parker, Cornelia 1956- (Tate, 2022)
Cornelia Parker's art is about destruction, resurrection and transformation. Always driven by curiosity, she reconfigures familiar objects to question our relationship with the world, and engage with the important issues of our time, be it violence, ecology or human rights. 0This landmark publication charts Cornelia Parker's career to date, from early work to the iconic installations Cold Dark Matter: An Exploded View 1991, for which she had a garden shed blown up, and Perpetual Canon 2004, made up of brass band instruments, steamrollered flat, to the immersive War Room 2015 and on to new work, such as Island and Flag, made in 2022. The book also explores the full range of her practice, from her monumental collective embroidery, as well as her films and a wealth of her innovative drawings, prints and photographs. No other contemporary artist has worked so closely with such a wide range of individuals, groups and institutions: the British Army, The Royal Mint, Abbey Road Studios, prisoners, school children, The Daughters of the Republic of Texas, whistleblowers and the UK Parliament among many others. Featuring a new, extended interview with Tate Britain Director of Exhibitions and Displays Andrea Schlieker, as well as insights and reflections from a selection of writers and collaborators, Cornelia Parker is an authoritative and captivating survey of one of Britain's best-loved and most acclaimed artists. Exhibition: Tate Britain, London, UK (16.05.-16.10.2022)
Published on the occasion of the exhibition of the same name held at Tate Britain, London, 18 May to 16 October 2022
Keywords: Parker, Cornelia -- 1956-; Videokunst; Zeichnung; Parker, Cornelia / 1956- / Exhibitions; Parker, Cornelia; Art, Modern / Exhibitions; Art, British / Exhibitions; Exhibition catalogs; Ausstellungskatalog -- Tate Britain -- 16.05.2022-16.10.2022 -- London; Bildband